Insulin receptor Arg717 and IGF-1 receptor Arg704 play a key role in ligand binding and in receptor activation - Kertisová, Anna; Žáková, Lenka; Macháčková, Kateřina; Marek, Aleš; Šácha, Pavel; Pompach, Petr; Jiráček, Jiří; Selicharová, Irena (Open biology, 2023)
The insulin receptor (IR, with its isoforms IR-A and IR-B) and the insulin-like growth factor 1 receptor (IGF-1R) are related tyrosine kinase receptors. Recently, the portfolio of solved hormone-receptor structures has grown extensively thanks to advancements in cryo-electron microscopy. However, the dynamics of how these receptors transition between their inactive and active state are yet to be fully understood. The C-terminal part of the alpha subunit (αCT) of the receptors is indispensable for the formation of the hormone-binding site. We mutated the αCT residues Arg717 and His710 of IR-A and Arg704 and His697 of IGF-1R. We then measured the saturation binding curves of ligands on the mutated receptors and their ability to become activated. Mutations of Arg704 and His697 to Ala in IGF-1R decreased the binding of IGF-1. Moreover, the number of binding sites for IGF-1 on the His697 IGF-1R mutant was reduced to one-half, demonstrating the presence of two binding sites. Both mutations of Arg717 and His710 to Ala in IR-A inactivated the receptor. We have proved that Arg717 is important for the binding of insulin to its receptor, which suggests that Arg717 is a key residue for the transition to the active conformation.
Keywords: Insulin; receptor tyrosine kinase; receptor modification; Receptor, Insulin; Insulin-Like Growth Factor I; mutagenesis in vitro; Ligands; peptide hormone; receptor inzulinu; insulinu podobný růstový faktor I; Receptor, IGF Type 1; inzulin; structure–function; ligandy; elektronová kryomikroskopie; Cryoelectron Microscopy; receptor IGF typ 1